Kepatuhan Sharī’ah dalam Fundraising Zakat melalui E-Commerce - Elizatun, Elizatun; Zainur Ridho (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2024)
Abstract: Zakat fundraising has been available in e-commerce features. However, with the development of this technology, new challenges arise, especially related to sharī'ah compliance. Where zakat is a religious obligation, its management must also be in accordance with sharī'ah principles. Thus, the background of this study aims to analyze how sharī'ah compliance can be guaranteed in fundraising zakat through e-commerce. This research applies qualitative method with descriptive approach. The data collection is in the form of documentation and interviews. The results of this study show that the basic practice of fundraising zakat through e-commerce is by muzaki choosing the type of zakat that will be submitted to mustahik through amil institutions that have partnered on the platform. After the zakat funds obtained from e-commerce are collected, they will be handed over to zakat institutions to be given to mustahik as stipulated in Islamic sharī'ah. However, in terms of sharī'ah compliance which is seen from the fulfillment of the pillars and conditions of zakat, transparency and accountability, and free from elements of usury, fundraising zakat through e-commerce is not yet in accordance with Islamic principles, which is one of them because the policies between e-commerce are different. So it is necessary to harmonize the regulations of the zakat institution. Keywords: sharī'ah compliance; zakat fundraising; e-commerce. Abstrak: Fundrasing atau penggalangan dana zakat telah tersedia pada fitur-fitur e-commerce. Namun dengan perkembangan teknologi ini, muncul berbagai tantangan baru, terutama terkait kepatuhan sharī’ah. Dimana zakat sebagai kewajiban agama, pengelolaannya juga harus sesuai dengan prinsip-prinsip sharī’ah. Dengan demikian, latar belakang kajian ini bertujuan untuk menganalisis bagaimana kepatuhan sharī’ah dapat terjamin dalam fundraising zakat melalui e- commerce. Penelitian ini menerapkan metode kualitatif dengan pendekatan deskriptif. Pengumpulan datanya berupa dokumentasi dan wawancara. Hasil dari penelitian ini menunujukkan bahwa praktik dasar fundrasing zakat melalui e-commerce yaitu dengan cara muzaki memilih jenis zakat yang akan diserahkan kepada mustahik melalui lembaga amil yang telah bermitra di paltform tersebut. Setelah dana zakat yang diperoleh dari e-commerce tersebut terkumpul, maka akan diserahkan kepada lembaga zakat untuk diberikan pada para mustahik sebagaimana ketentuan dalam sharī’ah Islam. Akan tetapi dalam hal kepatuhan sharī’ah yang dilihat dari terpenuhinya rukun dan syarat zakat, transparansi dan akuntabilitas, serta bebas dari unsur riba, fundrasing zakat melalui e-commerce belum sesuai dengan prinsip Islam, yang mana hal ini salah satunya karena kebijakan antar e-commerce berbeda-beda. Sehingga perlu penyelarasan peraturan dari lembaga zakat. Kata Kunci: kepatuhan sharī’ah; fundraising zakat; e-commerce.